Knowledge and attitudes of Peruvian dental students toward caring for people with HIV/AIDS - Freddy Ronald Valdez Jurado; Mariaelena Moscoso Sanchez (Editorial Ciencias Médicas, 2022)
Introduction: To the WHO, education is an important strategy in the fight against HIV/AIDS. The Organization recommends that emphasis is made on the training of health professionals in the comprehensive management of the people affected with quality, ethics and dignity. Objective: Evaluate the knowledge and attitudes of dental students toward caring for people with HIV/AIDS. Methods: Of the total 588 dental students attending a Peruvian public university in the year 2018, a sample of 235 was selected by probabilistic sampling. A 30-item questionnaire was used to collect data about sociodemographic characteristics and level of knowledge, dividing the scores into Good (≥ 20), Fair (15-19) and Poor (< 15). Attitudes were measured on a 20-item scale, and the scores obtained were classified as Favorable (70-100), Indifferent (50-69) or Unfavorable (< 50). A pilot study conducted with 60 students obtained a K-R reliability grade of 0.87 for the knowledge questionnaire and a Cronbach's alpha of 0.89 for attitudes. Results: 57% (CI 95%: 50.7-63.4%) of the students showed a good level of knowledge (≥ 20 points), whereas the most common attitude was Indifferent in 79.6%. The knowledge score of students attending clinical courses was statistically higher than that of students in preclinical courses (p < 0.05). A significant linear relationship was found between attitude and knowledge scores (rho = 0.23; p < 0.001). Conclusions: The students obtained good knowledge scores, but attitudes toward the care of HIV/AIDS patients are indifferent. Knowledge and attitudes scores are linearly correlated. Attending clinical courses was associated to the level of knowledge, not to attitudes.